A new view on molecular genetic features of stomach cancer - A. A. Mashukov; S. I. Kirkilevsky (Zaporožskij Medicinskij Žurnal)
The purpose of this article was to write a literature review on the possibility of genetic typing of patients with stomach cancer at the current stage of the domestic molecular genetic laboratory service development.